Gray wolf packs and human-caused wolf mortality ... - Cassidy, Kira; Borg, Bridget; Klauder, Kaija; Sorum, Mathew; Thomas-Kuzilik, Rebecca; Dewey, Sarah; Stephenson, John; Stahler, Daniel; Gable, Thomas; Bump, Joseph; Homkes, Austin; Windels, Steve; et al. (Dryad, 2022)
Gray wolves (Canis lupus) are group-living carnivores that travel over large areas and are one of the most controversial species in North America. Gray wolf management over the last century has ranged from eradication by nearly any means to preservation under the Endangered Species Act to state-managed which often includes limited hunting and, in some areas, population reduction. Management decisions are complicated by transboundary movements of wildlife, especially when the bordering agencies have disparate goals or mandates. This data is specific to gray wolves and packs using five National Park Service (NPS) units (years of data): Denali National Park and Preserve (33 years), Grand Teton National Park (23 years), Voyageurs National Park (12 years), Yellowstone National Park (27 years), and Yukon-Charley Rivers National Preserve (23 years). This dataset features two measures of gray wolf biological processes, pack persistence and reproduction, and was used to determine the impacts of anthropogenic ... : All data were collected by NPS staff and partners by deploying radio collars on each wolf pack using the National Park unit. Wolf packs were tracked aerially several times per month to determine persistence through time. Pack size was recorded during tracking. For each biological year a pack persisted, they were given a pack-year entry. Reproduction was determined through localization around a den or visual of at least one pup during the biological year. Human-caused mortalities were recorded and confirmed with necropsies and other wildlife official reports and then assigned to a specific pack-year. ...